Beyond democracy? Towards a post-democratic vision of governance - Anthony Joseph Carroll (Cauriensia)
This essay explores elements of a solution to the crisis of the current degrading of contemporary democracies through populism. It does this through arguing that the political transition from kingship to democracy has neglected important resources that are once again required for governance in the contemporary era. In recovering these resources of a vocational mandate, a teleological orientation and an exemplary witness, I conclude that together with developing new approaches to the cultivation of leaders, through critically adapting the ancient insights of Plato’s formation of political leaders, we can open up currently unrealised potential for moving beyond the blockages of secular democracies as exemplified by the rise of charismatic demagogues. Employing the model of the Deuteronomic King, I illustrate how a religiously informed institution of governance can preserve the positives of the secular modern democratic experiments and move beyond them in a post-democratic model of governance. This vision is motivated by a kenotic teleology of love that is anchored in both the person and the institution of the exemplary model of the leader.